Brain MRI Volumetry Analysis in an Indonesian Family of SCA 3 Patients: A Case-Based Study - Sobana, Siti Aminah; Huda, Fathul; Hermawan, Robby; Sribudiani, Yunia; Koan, Tan Siauw; Dian, Sofiati; Ong, Paulus Anam; Dahlan, Nushrotul Lailiyya; Utami, Nastiti; Pusparini, Iin; Gamayani, Uni; Mohamed Ibrahim, Norlinah; et al. (Frontiers in Neurology, 2022)
Introduction Spinocerebellar ataxia type-3 (SCA3) is an adult-onset autosomal dominant neurodegenerative disease. It is caused by expanding of CAG repeat in ATXN3 gene that later on would affect brain structures. This brain changes could be evaluated using brain MRI volumetric. However, findings across published brain volumetric studies have been inconsistent. Here, we report MRI brain volumetric analysis in a family of SCA 3 patients, which included pre-symptomatic and symptomatic patients. Methodology The study included affected and unaffected members from a large six-generation family of SCA 3, genetically confirmed using PolyQ/CAG repeat expansion analysis, Sanger sequencing, and PCR. Clinical evaluation was performed using Scale for the Assessment and Rating of Ataxia (SARA). Subjects' brains were scanned using 3.0-T MRI with a 3D T1 BRAVO sequence. Evaluations were performed by 2 independent neuroradiologists. An automated volumetric analysis was performed using FreeSurfer and CERES (for the cerebellum). Result We evaluated 7 subjects from this SCA3 family, including 3 subjects with SCA3 and 4 unaffected subjects. The volumetric evaluation revealed smaller brain volumes (p < 0.05) in the corpus callosum, cerebellar volume of lobules I-II, lobule IV, lobule VIIB and lobule IX; and in cerebellar gray matter volume of lobule IV, and VIIIA; in the pathologic/expanded CAG repeat group (SCA3). Conclusion Brain MRI volumetry of SCA3 subjects showed smaller brain volumes in multiple brain regions including the corpus callosum and gray matter volumes of several cerebellar lobules.